Needles in the ritual of cattle-breeding magic of the Volyn inhabitants - Pozhodzhuk, Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
Purpose: based on field ethnographic materials collected by the author, to describe the cattle-breeding rites associated with the use of needles (“strain milk on needles”, “cook a strainer with needles”) on the historical and ethnographic territory of Volyn, and to find out their regional peculiarity. Research methodology is based on the comparative historical and descriptive methods, principles of historicism and objectivity. The main material for this study was collected by the author during the field historical and ethnographic expeditions on the territory of Volyn using the pre-compiled thematic program questionnaire. Scientific novelty. For the first time, one of the important fragments of the spiritual culture of Volyn inhabitants has been substantially described in detail. The rite of “straining milk on needles” was considered in some professional scientific studies that deal with the traditional folk culture of the Slavs, so far in passing. Moreover, even sporadic mentions of it usually do not apply to Volyn as a historical and ethnographic region of Ukraine. The new archival sources put into scientific circulation will promote further study of demonological, calendar-household and cattle-breeding features of the folk culture of Ukrainians. Conclusions. A needle is the main object in the cattle-breeding magic of Volyn inhabitants, it helps not only to recognize a witch but to get rid of her harmful influence on cattle and milk. The rite of “straining milk on needles” (to cook a strainer with needles) was practiced on the territory of historical ethnographic Volyn everywhere. However, it was marked by a variety of options, which are more a consequence of the personification of respondents than a reflection of local specificity. The action with needles was rarely dedicated to one of the holidays of the folklore calendar; it was mostly an occasional phenomenon. The needle was in the past and is still the main object (sporadically, a sickle and a knife were also used), owing to which the Ukrainians of historical and ethnographic Volyn not only recognized the witch, but also made her vulnerable. The rite with needles, fire and a strainer gave the possibility to get rid of the harmful influence of the witch under some favourable circumstances. This process was quite painful for her, people believed that after the rite of staining milk on needles the witch should be burned and stabbed inside. Moreover, the witch (as an extremely unwanted guest) had every chance to feel the wrath of the man of the house - the owner of the injured cow and to suffer physically.